Metampicillin is a cyclic aminal produced by reaction of ampicillin with formaldehyde - Reinbold, Raphael (Sci Rep, 2020)
Metampicillin is a β-lactam antibiotic that is prepared by the reaction of ampicillin with formaldehyde. Although metampicillin has been studied for treatment of infections in animals and humans, its structure has been unclear. We report NMR studies revealing that metampicillin contains a formaldehyde-derived cyclic aminal. NMR time-course experiments with excess formaldehyde in solution show formation of another product with an additional exocyclic hemiaminal group formed by reaction with the cyclic aminal nitrogen. The exocyclic hemiaminal group is readily removed by reaction with the formaldehyde scavenger 1,3-cyclohexanedione, whereas the cyclic aminal methylene exhibits greater stability. The overall results assign the structure of metampicillin as containing a cyclic aminal and further reveal the potential for complexity in the reaction of formaldehyde with biomedicinally relevant molecules.